تأهيل المؤسسات الصغيرة والمتوسطة الجزائرية في ظل الانضمام المرتقب إلى المنظمة العالمية للتجارة - عناني، ساسية; نعمون، وهاب (كلية المنصور الجامعة, 2015)
The pursuit of the Algerian economy to integrate into the new global trading system Through to join upcoming to World Trade Organization. Constitutes a challenge for small enterprises and the Algerian medium, both at the level of diversification of markets or product diversification, Considering that join forces to open markets to facilitate the flow of goods and services across international borders and to the lack of international intervention and the freedom of trade, leading to heightened competition through increased presence of foreign institutions to maintain its market share. Therefore look to the future prospects of this join requires put a planned an ambitious and effective to restructure SMEs and rehabilitated so that they can gain a competitive capability enabling it to withstand the shock of integration, and strengthen its presence on the level of foreign markets.
إن سعي الاقتصاد الجزائري إلى الاندماج في النظام التجاري العالمي الجديد من خلال الانضمام المرتقب إلى المنظمة العالمية للتجارة، يشكل تحديا للمؤسسات الصغيرة والمتوسطة الجزائرية، سواء على مستوى تنويع الأسواق أو تنويع المنتجات، باعتبار أن الانضمام يفرض فتح الأسواق لتسهيل تدفق السلع والخدمات عبر الحدود الدولية وإلى عدم التدخل الدولي وحرية التجارة، مما يؤدي إلى اشتداد المنافسة من خلال تزايد وجود المؤسسات الأجنبية للحفاظ على حصتها في السوق. وعليه فإن التطلع إلى آفاق مستقبلية من خلال هذا الانضمام يتطلب وضع مخططا طموحا وفعالا لإعادة هيكلة المؤسسات الصغيرة والمتوسطة وتأهيلها حتى تستطيع إكتساب قدرة تنافسية تمكنها من الصمود أمام صدمة الإندماج، وتقوي وجودها على مستوى الأسواق الخارجية.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- المنظمة العالمية للتجارة -- العولمة -- التحولات الإقتصادية -- مستخلصات الأبحاث -- الجزائر -- المجتمع الجزائري